Factors Associated with Diarrheal Dehydration in Toddlers at Kalijudan Health Center Work Area - Meivi Yusinta Christy (Jurnal Berkala Epidemiologi, 2014)
One of the health problems of toddlers in Indonesia that still often occurs is diarrhea. Diarrhea is a disease that can cause death. The main cause of diarrhea death is dehydration due to loss of fluid and electrolytes through feces. Based on the monthly diarrhea report Public health center (PHC) of Kalijudan in 2013 found toddlers aged 1-4 years who suffered dehydration due to diarrhea. This study aims to analyze the relationship between characteristics and knowledge of mothers of children under five with the incidence of diarrhea dehydration in children under five in the PHC of Kalijudan’s working area, Surabaya. This research included analytic observational with a case-control design. Research subjects were drawn from the population by simple random sampling. Samples obtained were 30 case groups and 30 control groups. The independent variables of the study are the characteristics of mothers of children under five (age, education, work status, family income) and mother's knowledge. Primary data collection was carried out using a questionnaire. Data analysis uses Chi-square statistical tests. The results of the bivariate analysis revealed that the variables associated with the incidence of diarrhea dehydration in toddlers were working status of toddlers (p = 0.010), and knowledge of toddlers (p = 0.002). There was no relationship between the age of the mother of children under five (p = 0.779), education of mother of children under five (p = 0.797), and family income (p = 0.430). The conclusion that can be drawn is the working status and knowledge of toddler mothers significantly related to the incidence of diarrhea dehydration in toddlers. There is a need for education or health promotion for mothers of children under five about the proper management of diarrhea with seven diarrhea prevention interventions.